Anegdoty, humoreski i zarty ludu slaskiego - Widera, Aleksander (Katowice : Slaski Instytut Naukowy, 1983)
A collection of anecdotes and jokes from the Silesian region of Poland.
Keywords: Folklore -- Silesia; Polish wit and humor -- Silesia